Cluster Model for Establishing Special Economic Zones in Ukraine under Modern Conditions (Global Experience) - Borzenko, O.; Kuznietsova, N.; Tkachuk, I.; Hlazova, A. (Академик Е.А. Бөкетов атындағы Қарағанды университеті, 2024)
Abstract Object: Clusters are a relatively new form of organization, risk and profit sharing, and competitiveness enhancement for both the global and Ukrainian economies. The potential of the cluster development model is significant, and, most importantly, it has been justified in developed countries worldwide. In particular, global practice confirms that the functioning of the most prosperous economies is supported by advantages in modern production technologies and management. Therefore, successful development of any level is possible through the comprehensive application of modern strategic management concepts. Thus, the object of the study is to reveal and substantiate the effectiveness of cluster model in establishing special economic zones in Ukraine. Methods: The paper uses general scientific and special methods, that are: the dialectical method of understanding cluster model for establishing special economic zones; comparative analysis methods; methods of empirical research, methods of statistical and structural analysis; methods of historical and logical analysis; identifying individual parts of an object, methods of system approach, identifying cause-and-effect relationships. Findings: Custers are established on the base of a unique internal environment and infrastructure specific to a particular region. This allows leveraging the competitive advantages of enterprises in a specific area through integration. A cluster serves as a stimulus for economic development, and regionalism forms the basis for its sustainable growth. Regionalism is of great significance in selecting priority investment areas, as it can influence the level of uncertainty risk during the assessment of regional investment projects. Its effectiveness is confirmed by cluster development of the child nutrition project presented in the paper (Ivano-Frankivsk region, Ukraine). Conclusions: Cluster approach makes it possible to use available resources more efficiently. The cluster approach is connected with the policy of capacity-building as well as increasing competition profitability of national economies. There are also some cluster formations on the territory of Ukraine. Сluster is a convenient form of organizing a free economic zone. At the same time, each government develops its own approaches to the creation of clusters and regulation of their activities, accordingly, organizes the activities of those responsible for the implementation of the national strategy of sustainable competitive development.
Қазіргі жағдайда Украинада арнайы экономикалық аймақтарды құрудың кластерлік моделі (әлемдік тәжірибе)
Кластерная модель создания специальных экономических зон в Украине в современных условиях (мировой опыт)
Keywords: cluster; cluster model of the economy; policy; strategy; free economic zone